2013
DOI: 10.1371/journal.pone.0055703
|View full text |Cite
|
Sign up to set email alerts
|

Human 14-3-3 Paralogs Differences Uncovered by Cross-Talk of Phosphorylation and Lysine Acetylation

Abstract: The 14-3-3 protein family interacts with more than 700 different proteins in mammals, in part as a result of its specific phospho-serine/phospho-threonine binding activity. Upon binding to 14-3-3, the stability, subcellular localization and/or catalytic activity of the ligands are modified. Seven paralogs are strictly conserved in mammalian species. Although initially thought as redundant, the number of studies showing specialization is growing. We created a protein-protein interaction network for 14-3-3, kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 51 publications
0
59
0
Order By: Relevance
“…Seven isoforms of 14-3-3 in humans and several hundreds of 14-3-3 binding partners have been identifi ed to date. These proteins are involved in diverse processes like regulation of the cytoskeleton, GTPase function, membrane signaling, cell fate determination, response to insulin and TNF α , cell cycle progression, and apoptosis (Uhart & Bustos, 2013). Interestingly, two of the motifs phosphorylated by AKT2 are putative 14-3-3 binding sites raising the possibility that an interaction with 14-3-3 might be involved in regulating PKP1.…”
Section: Regulation Of Multifunctional Pkps By Phosphorylationmentioning
confidence: 99%
“…Seven isoforms of 14-3-3 in humans and several hundreds of 14-3-3 binding partners have been identifi ed to date. These proteins are involved in diverse processes like regulation of the cytoskeleton, GTPase function, membrane signaling, cell fate determination, response to insulin and TNF α , cell cycle progression, and apoptosis (Uhart & Bustos, 2013). Interestingly, two of the motifs phosphorylated by AKT2 are putative 14-3-3 binding sites raising the possibility that an interaction with 14-3-3 might be involved in regulating PKP1.…”
Section: Regulation Of Multifunctional Pkps By Phosphorylationmentioning
confidence: 99%
“…Are Acetylated-Phosphorylation of Ser 58 on 14-3-3 was shown to have a role in its self-dimerization (31), and acetylation of 14-3-3 on Lys 49 inhibited the phosphorylation-dependent interactions of this protein with its targets (35). In this study, we developed TAT peptides to compete with Ser 58 phosphorylation (TAT-14-3-3␥ Ser 58 ) and Lys 49 acetylation (TAT-14-3-3␥ Lys 49 ) sites to further assess their function in steroidogenesis (Fig.…”
Section: -3-3␥ Homodimers Are Phosphorylated and Monomersmentioning
confidence: 99%
“…Indeed, acetylation of key lysine residues in vivo indicates a novel regulatory mechanism of 14-3-3 function as this residue is located in the 14-3-3 monomer amphipathic groove through which they bind to their targets. Furthermore, Uhart and Bustos (13) reported cross-talk between 14-3-3 protein acetylation and phosphorylation in which acetylation of 14-3-3⑀ on Lys 49 inhibits the phosphorylation-dependent interactions of this protein with specific targets (35). In the present study, we investigated the effect of 14-3-3␥ acetylation and/or phosphorylation on STAR binding and 14-3-3␥ homodimerization during steroidogenesis.…”
mentioning
confidence: 90%
“…Early investigations performed on rat HspB6 indicated that this protein forms interconvertible oligomers with molecular weights of 43-67 and 300-470 kDa (Kato et al 1994 ;van de Klundert et al 1998 ). Analysis of crude muscle extract by sizeexclusion chromatography or sucrose density gradient detected HspB6 in fractions with apparent molecular weight in the range of 68-540 kDa (Kato et al 1994 ;Brophy et al 1999a ).…”
Section: Molecular Structure and Physico-chemical Properties Of Hspb6mentioning
confidence: 99%
“…ability to prevent aggregation of partially denatured or unfolded proteins, is common for all small heat shock proteins (McHaourab et al 2009 ;Vos et al 2008 ;Basha et al 2012 ). However, originally in vitro experiments performed with rat HspB6 indicated that the chaperone-like activity of this protein was lower than that of α-crystallin (van de Klundert et al 1998 ). Later studies performed on human HspB6 have shown that depending on the nature of model protein substrate the chaperone-like activity of human HspB6 is comparable to that of αB-crystallin (Bukach et al 2004 ;Mymrikov et al 2010 ;Datskevich et al 2012b ).…”
Section: Chaperone-like Activity and Probable Participation Of Hspb6 mentioning
confidence: 99%